2015
DOI: 10.1186/s13052-014-0107-1
|View full text |Cite
|
Sign up to set email alerts
|

Meningoencephalitis caused by Plesiomonas shigelloides in a Chinese neonate: case report and literature review

Abstract: The most usual presentation of Plesiomonas shigelloides infection is an acute gastroenteritis, and extraintestinal manifestations are extremely rare. We reported the first neonate with P. shigelloides meningoencephalitis in China and reviewed the twelve cases previously reported. Our report adds further awareness on Plesiomonas shigelloides meningoencephalitis in neonate and points out the importance of an early diagnosis and the use of sensitive antibiotics treatment to this fatal infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…Table 7 summarizes some retrospective reviews of cumulative data on cases of Plesiomonas sepsis reported in the English literature (29,108,137). Based upon the review of Woo (108) and several published case reports since 2005, there are now over 40 cases of P. shigelloides bacteremia in the literature (111,114,138,139). This is almost double the number reported by Lee (137) …”
Section: Septicemia and Cns Diseasementioning
confidence: 70%
See 4 more Smart Citations
“…Table 7 summarizes some retrospective reviews of cumulative data on cases of Plesiomonas sepsis reported in the English literature (29,108,137). Based upon the review of Woo (108) and several published case reports since 2005, there are now over 40 cases of P. shigelloides bacteremia in the literature (111,114,138,139). This is almost double the number reported by Lee (137) …”
Section: Septicemia and Cns Diseasementioning
confidence: 70%
“…Slightly under one-third of all bacteremias occur in neonates with meningitis or meningoencephalitis (114). Almost all of these cases of infection occur within the first 5 days of life and appear to have been vertically transmitted (perinatal) rather than transplacental (114). Plesiomonas has only been recovered from maternal feces on three occasions.…”
Section: In 1996mentioning
confidence: 99%
See 3 more Smart Citations